Thermal Cracking of Massive Concrete Structures State of the Art Report of the RILEM Technical Committee 254-CMS - Fairbairn, Eduardo M.R.; Azenha, Miguel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a State of the Art Report (STAR) produced by RILEM Technical Committee 254-CMS 'Thermal Cracking of Mas-sive Concrete Structures'. Several recent developments related to the old problem of understanding/predicting stresses originated from the evolution of the hydration of concrete are at the origin of the creation this technical committee. Having identified a lack in the organization of up-to-date scientific and technological knowledge about cracking induced by hydration heat effects, this STAR aims to provide both practitioners and scientists with a deep integrated overview of consolidated knowledge, together with recent developments on this subject.
Preface -- Acknowledgements -- Introduction, by Eduardo Fairbairn and Miguel Azenha -- Hydration and heat development, by Laurie Lacarrière, Agnieszka Knoppik, Wilson Ricardo Leal da Silva, Tulio Honorio, Vit Šmilauer, Shingo Asamoto, and Eduardo Fairbairn -- Thermal properties, by Mateusz Wyrzykowski, Agnieszka Knoppik, Wilson R. Leal da Silva, Pietro Lura, Tulio Honorio de Faria, Yunus Ballim, Brice Delsaute, Stéphanie Staquet, and Miguel Azenha -- Mechanical properties, by Farid Benboudjema, Jérôme Carette, Brice Delsaute, Tulio Honorio de Faria, Agnieszka Knoppik, Laurie Lacarrière, Anne Neiry de Mendonça Lopes, Pierre Rossi7, and Stéphanie Staquet -- Mixture proportioning for crack avoidance, by Stéphanie Staquet, Brice Delsaute, Eduardo Fairbairn, Roberto Torrent, Agnieszka Knoppik, Neven Ukrainczyk, and Eduardus A.B. Koenders -- Temperature control, by Miguel Azenha, Ioannis P Sfikas, Mateusz Wyrzykowski, Selmo Kuperman, Agnieszka Knoppik -- Numerical modelling, by Francesco Pesavento, Agnieszka Knoppik, Vit Šmilauer, Matthieu Briffaut, and Pierre Rossi -- Cracking risk and regulations, by Agnieszka Knoppik, Jean-Michel Torrenti, Shingo Asamoto, Eduardus Koenders, Dirk Schlicke, and Luis Ebensperger -- On-site monitoring of mass concrete, by Dirk Schlicke, Fragkoulis Kanavaris, Rodrigo Lameiras , Miguel Azenha -- Sustainability aspects in mass concrete, by Neven Ukrainczyk and Eduardus A.B. Koenders -- Terminology, Symbols and Acronyms. .
Keywords: Building materials; Materials -- Analysis; Mechanics, Applied; Solids; Building Materials; Characterization and Analytical Technique; Solid Mechanics